The contribution of an urban gravity survey to the determinable perspective of Athens city (Greece) underground structure - Dilalos, Spyridon; Alexopoulos, John D. (SN Applied Sciences, 2020)
An urban gravity survey with more than 1120 measurements was carried out in order to adumbrate the deeper subsurface of Athens city basin. The aim was to gather quantitative information of the subsurface structure derived from the acquisition of gravity measurements. At first, a gravity base network has been established for the data collection. The standard data reduction has been carried out along with an additional Building Correction that has been calculated due to the urban characteristics. Subsequently, the residual anomaly was isolated with the contribution of the Fourier filters. The Euler deconvolution has been applied, with two different techniques, providing depth solutions for the residual maps. Based on these maps, we managed to retrieve quantitative information for the depths of anomalous sources, ranging between 500 and 3760 m. Moreover, unconstrained three-dimensional density models of the area have been constructed in order to obtain a good image of the subsurface, up to depths of 4500 m. For each three-dimensional density model, we provide a couple of images; one illustrating only the structures of lower densities and one other only with the structures of higher densities, in an effort to delineate better the tectonic structures. Finally, two geophysical-geological profiles (2.75D) have been constructed, along which the geotectonic regime of the subsurface seems to be adumbrated in a better way. Major known tectonic structures of Athens basin have been identified beneath the surface.